Edukasi Self-Management terhadap Pengaturan Pola Makan dan Konsumsi Obat pada Pasien DM Tipe 2 - Putri Drissianti; Marlina Marlina; Hajjul Kamil (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effectiveness of self-management education on drug consumption and diet management in patients with Type 2 DM at the East Aceh Health Center. The research method used is quantitative research with a quasi-experimental design. The results showed that the average pretest and posttest results were 27.24 and 29.51 posttest, 8.18 pretest, and 11.10 posttest results. The statistical test results showed a significant difference between the pretest and posttest of dietary adjustments and drug consumption. There is an increase in dietary regulation and drug consumption after self-management education. In conclusion, the provision of self-management education effectively regulates diet and drug consumption in patients with Type 2 DM in the working area of the Idi Rayeuk Health Center. Keywords: Type 2 Diabetes Mellitus, Self-Management Education, Self-care